China’s regulatory respond to plastic pollution: Trends and trajectories - Fürst, Kathinka; Feng, Yidi (Frontiers in Marine Science, 2022)
Despite China having an international reputation as one of the largest contributors to plastic pollution in the world’s oceans, research analyzing China’s regulatory approach to governing plastic has been limited and fragmented, and as such, little is known about trends and trajectories dominating China’s plastic policy landscape. In this paper, we seek to address this gap in the literature through the construction and analysis of a complete inventory of China plastic-related policies from 1 January 2000 to 30 June 2021. Utilizing NVIVO (a qualitative analysis software), our analysis of 231 Chinese plastic policy documents shows that China’s serious and concentrated effort to governing plastics really took off in the year 2016. From 2016, China saw a rapid increase in the attention paid to plastic pollution in the regulatory realm. In 2000, there were only four plastic-pertinent policies, but by the first half of 2021, this number has grown to 41, representing an increase of 925%. In this period, China has also significantly transformed its approach to governing plastics; not only has the goal and purpose of regulating plastic increased in complexity, but the type of plastics targeted and the different aspects of the plastic value chain included in various policies have become increasingly comprehensive over time. Concurrently, the deployment of different types of regulatory instruments utilized for the purpose of governing plastics in China has become much more diversified, with a major focus on prohibitive bans and information campaigns currently dominating Chinese plastic policy instruments. Economic policy instruments, on the other hand, especially economic incentives, have only recently been gaining popularity. Finally, today, most government agencies have published policies that are relevant to the regulation of plastic pollution control and prevention in China. Despite the massive increase in plastic pertinent policies in China, the predominant focus is still on back-end policy, with little regulatory attention on the upstream part of the plastic lifecycle (i.e., prodigious production of plastics). China’s fairly recent plastic policy awakening should be understood in light of China’s focus on the circular economy, the county’s ramping up of regulatory focus, and fiscal investment in solid waste management and pertinent infrastructure. Towards the end of the paper, we point to some possible trajectories for the China plastic policy landscape, highlighting the synergies between reducing plastic production, consumption, and waste treatment and China’s carbon neutrality ambition, as well as predicting a stronger policy focus and emphasis on plastic cleanup efforts.